PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN DENGAN METODE SCRAMBLE PADA SISWA KELAS IV SD NEGERI NUSA HARAPAN PERMAI MAKASSAR - Andriani, Reski Sural; Yunus, Muhammad; Asdar (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2020)
Type of this research was Classroom Ation Research which based on several steps, such as planning, action implementation observation, evaluation, and reflection. Subject of the research were IV class students SD Nusa Harapan Permai Makassar as many as 23 students. Data collection used observation and the next test analyzed by descriptive method. The result of the research showed that the application of Scramble Method for Increasing of Comprehension Reading Skill students could improve learnig result of students in IV class SD Nusa Harapan Permai Makassar. In this case based on the improvement average value of learning result from 69.13% in cycle I became 78.26% in cycle II and the increase of average value is eleven percent. So, this research is considered successful.